Implementation of character education in establishing a holistic personality at SMAN 1 Enam Lingkung - Hardi, Etmi; Jamaris, Jamaris; Solfema, Solfema (CAHAYA PENDIDIKAN, 2023)
The purpose of this study is to understand the implementation of character education in the formation of students' holistic personality. The method used is qualitative research carried out at SMAN 1 Enam Lingkung. To obtain information, direct observation activities were carried out to the school and then searched for various literature and conducted interviews with key informants consisting of the principal, vice principals, homeroom teachers, teachers and students. After the interview activity was carried out, the researcher processed the data using inductive techniques with steps consisting of data reduction activities, data presentation and data verification. The results of this study are: (1) there are two strategies in the implementation of character education in SMAN 1 Enam Lingkung, namely internal and external; (2) the form of internal strategy can be pursued through five pillars, namely teaching and learning activities in the classroom, self-development activities before entering the lesson time at start, daily activities at school, habituation activities, co-curricular activities, and extra-curricular activities; and (3) external strategies can be implemented by cooperating with parents or guardians of students and the community.